Visible light driven amide synthesis in water at room temperature from Thioacid and amine using CdS nanoparticles as heterogeneous Photocatalyst. (22nd December 2017) - Das, Sudipto; Ray, Shounak; Ghosh, Abhisek Brata; Samanta, Partha Kumar; Samanta, Suvendu; Adhikary, Bibhutosh; Biswas, Papu
Abstract : Highly efficient photocatalytic thioacid mediated amide synthesis at room temperature using CdS nanoparticles as photocatalyst was observed under a household 30 W CFL in water. The operationally mild reaction was tolerant to a number of functional group substitutions on amine and could be scaled up to gram. This heterogeneous photocatalyst was extremely stable and could easily be recovered by simple centrifugation for at least six recycling reactions without any significant loss of catalytic performance. The possible reaction mechanism for the photocatalytic thioacid mediated amide synthesis over the CdS semiconductor has also been proposed on the basis of experimental observations. Abstract : Efficient photocatalytic thioacid mediated amide synthesis at room temperature using CdS nanoparticles as photocatalyst has been performed under visible light irradiation in water.